Directional topography gradients drive optimum alignment and differentiation of human myoblasts - Almonacid Suarez, Ana Maria (J Tissue Eng Regen Med, 2019)
Tissue engineering of skeletal muscle aims to replicate the parallel alignment of myotubes on the native tissue. Directional topography gradients allow the study of the influence of topography on cellular orientation, proliferation, and differentiation, resulting in yield cues and clues to develop a proper in vitro environment for muscle tissue engineering. In this study, we used a polydimethylsiloxane‐based substrate containing an aligned topography gradient with sinusoidal features ranging from wavelength (λ) = 1,520 nm and amplitude (A) =176 nm to λ = 9,934 nm and A = 2,168 nm. With this topography gradient, we evaluated the effect of topography on human myoblasts distribution, dominant orientation, cell area, nuclei coverage, cell area per number of nuclei, and nuclei area of myotubes. We showed that human myoblasts aligned and differentiated irrespective of the topography section. In addition, aligned human myotubes showed functionality and maturity by contracting spontaneously and nuclei peripheral organization resembling natural myotubes.